La diffusion de la publicité par les technologies de l’information et de la communication - BELIMANE, Yamina (Journal of Human Sciences, 2016)
Information communication technology ,constitute a media for as well as a new means which enhanced the filed of advertisement considerably in addition to that, It is an interactive form of communication which allows people dealing in commerce and industry to improve the sell of their products.Advertisement on the net represents the commercial basis of revenue of sponsors and of the contents and of the different means of research. it gives internet users accesses to sources of info and meant for free which is only possible thought his means .That is advertisement messages are today transmitted through internet in parallel with the traditional means communication.The right of advertisement, juridical arrangements and applicable legislation should cope with the change on economics, in life style, development in advertising techniques and new materials, like new information technologies and communication.